E-learning in COVID 19 period: first year students’ perspective: a web-based Google form descriptive study - C., Rose Davy; Mani, Koushiki (International Journal Of Community Medicine And Public Health, 2021)
Background: The current COVID-19 pandemic has drastically changed the paradigm of medical education. Face-to-face mode of teaching was the basis of traditional medical education. In this crisis situation, e-learning has become the only method of education for continuous learning. In this study, we attempt to find out the students’ perspective of various aspects of e-learning. Methods: For the purpose of the study, a questionnaire was prepared to understand student’s attitude towards e-learning, their likes and dislikes about e-learning and also suggestions from their end to improve the existing modes of e-learning. The set of questionnaire (Google forms) along with informed consent was shared via whatsapp group at the end of physiology theory teaching session. Results: 175 first year MBBS students gave their consent and participated in this study. The most preferred method of e-learning was power-point with recorded narration and the least preferred method was live classes. Poor connectivity issue is the major challenge faced by the students in our study. Conclusions: In this COVID-19 era, the future of medical education has changed forever. E-learning is the new normal method of teaching. In order to be effective, students require support from Government, faculties and parents.